Teaching foreign cultures in the english classroom in seventh grade at eudoro granada school. (2016)
This study aimed at investigating the impact of teaching foreign culture related subjects in developing of the students’ four skills, but mainly speaking as this investigation has a communicative approach to appeal the students’ interest. The research was carried out in seventh grade English and it was made observations to determine the group’s English level, attention length and performance. Then the students were introduced to culture related lesson plans. The study includes qualitative data. The data for this investigation was gathered through self assessment checklist and discussions about the content of the class with the students. The findings of the study showed that the implementation of culture based lesson plans that have a positive impact in the students’ four skills and oral production. Also the results of the analysis of the discussion after class indicated that the students had a positive attitude towards the classes and found the topics compelling, as the subjects were presented with different types of media and involved diverse skills.